Hubungan Paparan Pestisida Organofosfat dengan Laju Endap Darah (LED) pada Petani di Desa Sumberejo Kecamatan Ngablak Kabupaten Magelang (Association Between Exposure Organophosphate Pesticides with Erythrocyte Sedimentation Rate (ESR) Among Farmers In De - Utami, Desi Putri; Dangiran, Hanan Lanang; Darundiati, Yusniar Hanani (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Desa Sumberejo which the majority of population is vegetable farmers much found the sprayer farmers using pesticides type organophosphate. Spraying pesticides that not follows  the rules will result health effects to humans example incidence of poisoning on farmers and affects the blood profile of the farmers. The purpose of this research is to know the relation between exposure of organophosphate pesticide with erythrocyte sedimentation rate (ESR) on farmers in Desa Sumberejo, Kecamatan Ngablak, Kabupaten Magelang. The method used in this research is cross sectional with a population of 110 farmers and sample of 43 farmers obtained by purposive sampling technique of sampling.  This research and sample as many as 43 farmers obtained by purposive sampling technique of sampling. This research was implemented in April 2017. Statistical test results obtained upon the p-value > 0.05 to  the relationship between the working period, the use of the self protective tools, long work, the number of types of pesticides and the type of pesticide, spraying frequency, chollinesterase levels. While the test statistic between doses of pesticides with ESR his p-value < 0,05 that is 0,048. It can be concluded that there is no relationship between the working period, the use of the self protective tools, long work, the number of types of pesticides and pesticide spraying frequency, type, and chollinesterase levels with ESR and there is a relationship between the dose of pesticides with ESR on farmers in Desa Sumberejo.